HUBUNGAN TINGKAT KEPATUHAN MINUM OBAT PASIEN HIPERTENSI TERHADAP TEKANAN DARAH PASIEN HIPERTENSI DI RUMAH SAKIT PELABUHAN JAKARTA - Vidia Anwar; siti aisyah; doni iswandani; Halim, Marta; fitri putriani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
This research was conducted at Hospital X using quantitative descriptive methods with research instruments in the form of the ProMAS questionnaire. The sample collection technique used a purposive sampling method with a total sample of 96 respondents. The analysis used is the Spearman’s rho correlation test. The results showed that respondents who had high compliance were 43 people (44.79%), moderately high compliance was 48 people (50%), and medium low compliance was 5 people (5.21%) with controlled blood pressure of 64 people. and uncontrolled 32 people. Respondents who suffered from hypertension were dominated by women, 55 people (57.3%) with the highest level of education, namely high school graduates/equivalent, 44 people (45.83%). The largest age of respondents who experienced hypertension was 52 - 63 years old, 52 people (54.17%). The conclusion of this study is that there is a significant relationship between adherence to taking antihypertensive medication and the blood pressure of hypertensive patients with the Sig value. (2-tailed) 0.041 < 0.05 with a correlation value of -0.209, which means the level of relationship is weak with the direction of the relationship being negative, meaning that the higher the adherence to taking medication, the lower the blood pressure of hypertensive patients.